2005
DOI: 10.1080/00016470510030652
|View full text |Cite
|
Sign up to set email alerts
|

Femoral lengthening over an intramedullary nail using the external fixator

Abstract: Background The time for femoral lengthening is shortened if external fixation is combined with intramedullary nailing. However, several complications have been reported with this procedure.Patients and methods We retrospectively reviewed the outcome of femoral lengthening performed over an intramedullary nail using external fixation in 22 patients. These patients were followed for a mean of 3.2 (2-5.2) years. The mean age was 22 (13-35) years at the time of the index procedure. The mean lengthening was 5 (2.7-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
29
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(34 citation statements)
references
References 18 publications
5
29
0
Order By: Relevance
“…The DCI is 30-60 days/cm in the femur and varies according to disorder, age, location of osteotomy, whether the limbs underwent previous surgery, and the use of dynamization. [15][16][17][18] From the above values, we see that the pattern type and DCI are unrelated. The reason could be that the presence of both the external fixator and intramedullary nail give a great amount of stability to the femur during distraction, and, as soon as the distraction phase is over, the femur callus is further stabilized by interlocking distally and removal of the fixator.…”
Section: Discussionmentioning
confidence: 91%
“…The DCI is 30-60 days/cm in the femur and varies according to disorder, age, location of osteotomy, whether the limbs underwent previous surgery, and the use of dynamization. [15][16][17][18] From the above values, we see that the pattern type and DCI are unrelated. The reason could be that the presence of both the external fixator and intramedullary nail give a great amount of stability to the femur during distraction, and, as soon as the distraction phase is over, the femur callus is further stabilized by interlocking distally and removal of the fixator.…”
Section: Discussionmentioning
confidence: 91%
“…Nakase et al 26 in their series (n = 14 limbs; 7 femurs and 7 tibias) reported the complications of superficial pin tract infection (4 segments), deep infection (1 segment), secondary deformity in regenerate bone after lengthening (2 segments), and fracture after fixator removal (1 segment). Song et al 10 in their series of femoral lengthening over nail reported 3 cases of deep infection and required early removal of the nail. Ganger et al 25 in their series reported 36 implant-related complications.…”
Section: Discussionmentioning
confidence: 99%
“…9 However, serious complications such as deep infections, refractures, and axial deviation were still observed. 1012 …”
Section: Introductionmentioning
confidence: 99%
“…19 These techniques have shown to reduce the duration of time in external fixator, but are associated with complications such as failure or incarceration of the nail and osteomyelitis. 29,30 Our fracture rate of 4.5% remains acceptable without this combined technique, although it is an option to be considered in select cases. Also the bone healing index in our study was 47.2 days/cm which is similar to femoral lengthening over an intramedullary nail with an external fixator (43 days/cm).…”
Section: Discussionmentioning
confidence: 93%